Concentration Optimization Na2CO3 Alginates from Turbinaria sp. as Raw Material Electrolite Polymer for DSSC - Dinda Liyana; Nurhadini Nurhadini; Ristika Oktavia Asriza (Department of Chemistry - Universitas Bangka Belitung, 2021)
Polymer electrolyte DSSC is one component of the application can convert solar energy into electrical energy. The polymer electrolyte can be synthesized from brown seaweed Turbinaria sp. However, the optimization of alginate extraction has not been widely carried out, so the aim of this study was to determine the optimum conditions for variations in the concentration of Na2CO3 (3%, 5%, 7%) in extracts from Turbinaria sp as raw material for polymer electrolyte synthesis for DSSC. Alginate optimum extraction results known by percentage yield, moisture content and functional groups using FTIR analysis. The optimum conditions for alginate extraction from Turbinaria sp are Na2CO3 5% and a temperature of 60 oC with a yield of 23.81% and a moisture content of 8.1%. FTIR results also indicate the intensity of the strongest mannuronic seen at 822cm-1 wave numbers.